Detecting pulmonary oedema in lung resection patient through point‐of‐care lung ultrasonography. Issue 9 (22nd February 2022) - Zhao, Xiaoning; Liu, Yong; Sun, Mingyan; Wang, Yingying; Qian, Bailing
Abstract: Background: Postoperative pulmonary oedema is an outstanding postoperative complexity brought about by numerous etiological variables and which can be effectively recognized through careful control during the postoperative period. Lung ultrasound (LUS) was utilized for the non‐obtrusive recognition of pulmonary oedema. Semi‐quantitative visual LUS scores (visual LUS [V‐LUS]) in light of B‐lines correspond decently with pulmonary capillary pressure (PCWP) and extravascular lung water (EVLW). Methods: Seventy‐eight patients with pulmonary resection and pulmonary ultrasound at the time of treatment were examined. Cardiopulmonary echocardiography was performed on the first day before and after the operation, and the oxygenation index (PaO2 /FiO2 ) was measured after the operation. B‐lines from B‐score were measured through lung ultrasound. Each region was classified as "B0" if fewer than three B‐lines were identified in the entire intercostal space. "B1" if there were at least three B‐lines in at least one intercostal space, "B2" in the presence of the "white lung field". B‐score were recorded at baseline (T0, before operation), after 1 day (T1), after 2 days (T2), after 3 days (T3), after 5 days (T5), after 7 days (T7), after 9 days (T9). Statistical software was used for the measurement of statistical correlations. Results: (1) The total number of B‐lines is negatively correlated with oxygen and the index ( r = −0.50, p < 0.001). (2) The B‐score appeared significantly with 86% of T1 to T3 and disappeared in 83% from T7 to T9 existed in 17% (3). The logistic regression analysis showed that the surgical method influenced the total number of B‐lines. Conclusions: LUS optimizes treatment by identifying subclinical pulmonary oedema, which facilitates early detection of pulmonary oedema and improves the prognosis.